Quick and safe: why a k-wire-extension-block-fixation of a bony mallet finger is the favoured treatment - Stumpfe, Maximilian; Suffa, Nadine; Merkel, Pauline; Ludolph, Ingo; Arkudas, Andreas; Horch, Raymund E. (Archives of Orthopaedic and Trauma Surgery, 2024)
Introduction: Mallet fingers are the most common tendon injuries of the hand. Bony avulsion distal finger extensor tendon ruptures causing a mallet finger require special attention and management. In this monocentral study, we analyzed the clinical and individual outcomes succeeding minimal invasive k-wire extension block treatment of bony mallet fingers. Materials and methods: In a retrospective study, we sent a self-designed template and a QUICK-DASH score questionnaire to all patients, who were treated because of a bony mallet finger between 2009 and 2022 and fulfilled the inclusion criteria. A total of 244 requests were sent out. 72 (29.5%) patients participated in the study. Forty-five men and twenty-seven women were included. Results: 98.7% (n = 75) of the cases were successfully treated. Patients were highly satisfied with the treatment (median 8.0; SD ± 2.9; range 1.0–10.0). Based on the QUICK-DASH score, all patients showed no difficulties in daily life. The extent of avulsion did not influence the outcome. Conclusion: We conclude that the minimally invasive treatment of a bony mallet finger should be offered to every patient, because it is safe, fast, and reliable. Thus, we propose to perform extension-block pinning independently of the articular area.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Bony extensor tendon rupture; Intervention; Kirschner-wire-fixation; Mallet finger; Mallet fracture